2018
DOI: 10.1007/s00125-018-4727-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of plasma MR-proADM vs NT-proBNP for heart failure in people with type 2 diabetes: the SURDIAGENE prospective study

Abstract: MR-proADM is a prognostic biomarker for heart failure in people with type 2 diabetes but gives no significant complementary information on prediction of heart failure compared with NT-proBNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…After screening, a total of 18 studies 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 published between 2008 and 2021 were included in the review, with data from 999 167 unique patients with T2D. Of these 18 studies, 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 2 were identified by screening reference lists 20 and conference abstracts, 30 respectively. A flow diagram of study selection is shown in Figure 1 and the list of excluded full‐text citations is available in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening, a total of 18 studies 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 published between 2008 and 2021 were included in the review, with data from 999 167 unique patients with T2D. Of these 18 studies, 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 2 were identified by screening reference lists 20 and conference abstracts, 30 respectively. A flow diagram of study selection is shown in Figure 1 and the list of excluded full‐text citations is available in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…Together 15 multivariable prediction models 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 were assessed as 3 studies 30 , 31 , 32 exclusively performed external validation. Most modeling studies used randomized controlled trials (9 of 15) 15 , 16 , 17 , 19 , 20 , 21 , 22 , 25 , 28 for model development, 3 of which were the ACCORD (Action to Control Cardiovascular Risk in Diabetes) trial. 20 , 21 , 33 The median number of participants and events used for model development was 8756 (interquartile range, 5184‒16 013) and 258 (interquartile range, 223‒420), respectively (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Otro biomarcador pronóstico evaluado en el estudio Suivi Rénal, DIAbète de type 2 et GENEtique (SURDIAGENE) fue la región media-adrenomodulina (MR-proADM), pero en DM no aportó información predictiva significativa comparada con el NT-pro BNP, al igual que la troponina de alta sensibilidad 79,70 .…”
Section: B) Laboratoriounclassified